Compensatory Work Devotion: How a Culture of Overwork Shapes Women's Parental Leave in South Korea. Issue 4 (August 2022) - Oh, Eunsil; Mun, Eunmi
Despite growing concerns that parental leave policies may reinforce the marginalization of mothers in the labor market and reproduce the gendered division of household labor, few studies examine how women themselves approach and use parental leave. Through 64 in-depth interviews with college-educated Korean mothers, we find that although women's involvement in family responsibilities increases during leave, they do not reduce their work devotion but reinvent it throughout the leave-taking process. Embedded in the culture of overwork in Korean workplaces, women find it justifiable to use leave only when they are highly committed to work and adjust the length of leave to accommodate workplace demands. Upon returning to work, they try to compensate for their absence by working harder than before, thereby showing that they are more committed than their colleagues. Given this "compensatory" work devotion, women question their own entitlement in the workplace, and some quit when they cannot meet their goal of compensating by doing more than others. This study highlights how the workplace culture shapes women's work devotion during and after leave.